2011
DOI: 10.1002/ejic.201001080
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Electronic Properties of the Photoinduced States of the H‐Cluster in the [FeFe] Hydrogenase from D. desulfuricans

Abstract: [FeFe] hydrogenases belong to a class of enzymes that catalyze the reversible heterolytic splitting of molecular hydrogen. The structure of their active site is rather unusual consisting of a CN -and CO-coordinated [2Fe] subcluster connected to a ferredoxin-like [4Fe4S] subcluster through one of the Cys-S ligands. The iron, distal to the "cubane" has an open coordination site that is believed to be the substrate binding site. In the active forms of the H-cluster, this site can be inhibited by carbon monoxide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(76 citation statements)
references
References 36 publications
(92 reference statements)
8
68
0
Order By: Relevance
“…55 32,37,38,56 In H ox -CO, a strong inter-cluster exchange (95 cm À1 ) interaction is apparent, based on the 57 Fe hyperfine interaction data, which led us to speculate that the g z -component could be oriented along the intercluster axis. 25 Since in H ox and oxidized CrHydA1(pdt) the intercluster exchange interaction is much smaller (25 cm À1 ) and the spin density seems to be equally distributed over both iron atoms in [2Fe] H , it is reasonable to assume that the vector connecting Fe p and Fe d represents a local symmetry axis and defines the orientation of the g-tensor.…”
Section: Orientation Of the G-tensor Within The H-clustermentioning
confidence: 96%
“…55 32,37,38,56 In H ox -CO, a strong inter-cluster exchange (95 cm À1 ) interaction is apparent, based on the 57 Fe hyperfine interaction data, which led us to speculate that the g z -component could be oriented along the intercluster axis. 25 Since in H ox and oxidized CrHydA1(pdt) the intercluster exchange interaction is much smaller (25 cm À1 ) and the spin density seems to be equally distributed over both iron atoms in [2Fe] H , it is reasonable to assume that the vector connecting Fe p and Fe d represents a local symmetry axis and defines the orientation of the g-tensor.…”
Section: Orientation Of the G-tensor Within The H-clustermentioning
confidence: 96%
“…We thus have presented here the very first and unique probe to monitor the presence of 15 Hyperfine Coupling hydrogenase. Our data should provide a solid basis to screen 15 N-labeled potential precursors of adt 2− using the in vitro cellfree [FeFe] hydrogenase maturation methodology developed by Swartz and co-workers based on the combination of individually expressed maturases HydE, HydG, and HydF with unmaturated [FeFe] hydrogenase. The discovery of the precursor of adt 2− , the missing link of the [FeFe] hydrogenase maturation process, will hopefully allow a complete description of this fascinating biosynthetic pathway.…”
mentioning
confidence: 98%
“…In order to identify the nitrogen of the bridging amine using HYSCORE spectroscopy and distinguish its spectroscopic signature from that of the CN − nitrogens, we studied three isotopelabeled variants of the H-cluster ( 15 N-adt 2− /C 14 N − , 15 Nadt 2− /C 15 N − , and 14 N-adt 2− /C 15 N − ) and extracted accurate values of the hyperfine and quadrupole couplings of both CN − and adt 2− nitrogens. This will allow an evaluation of isotopologues of the H-cluster generated by in vitro bioassembly in the presence of various 15 8 It is believed that a similar assembly process occurs in vivo, where the binuclear subsite is first synthesized by the radical S-adenosylmethionine maturation proteins HydE and HydG and subsequently inserted into the unmaturated [FeFe] hydrogenase using the third maturation protein HydF. 3,9 The groups of Broderick and Roach demonstrated that the CN − and CO ligands of [2Fe] H are synthesized from the substrate tyrosine by HydG.…”
mentioning
confidence: 99%
“…In this case, an additional CO ligand occupies the open coordination site at the distal iron, forming an EPRactive CO-inhibited state (H ox -CO) (12,21). This additional CO ligand dissociates under illumination at cryogenic temperatures below 60 K. The resulting state of such photodissociation is the active oxidized state (H ox ) (8,12,22). For a summary of [FeFe]-hydrogenase redox states, see supplemental Fig.…”
mentioning
confidence: 99%